Implementasi Streaming Media untuk E-learning pada Aplikasi Moodle - Surjo, Gregorius Maria; Palit, Henry Novianus; Noertjahyana, Agustinus (Jurnal Infra, 2018)
Teaching and learning process are growing over time and technology behind it are growing too so that the process of learning with online media or often referred to as e-learning where provided media that can be accessed via the internet. This phenomenon is interesting to examine because some e-learning systems that exist today are not yet fully secure, in the sense that it is still easy to be disseminated without any copyright and not used wisely. The purpose of this research is to produce an application that can be used as a media for e-learning of streaming audio and video without storing the file on local cache device so that the file residing in e-learning media cannot be disseminated and be used wisely. As a research methodology using deductive qualitative method, data collective process is done by literature study, interview, and observation. After the data collected, will result e-learning software based on website and mobile that can be used to stream media files without downloading it. The result of this test and analyze shown that streaming with RTSP protocol is can be used into e-learning software with a limited users.